VARIABILITY OF SEA SURFACE TEMPERATURE AND SALINITY IN MAKASSAR STRAIT DURING THE LAST GLACIAL MAXIMUM - Larasati, Oktavira Dwi Demia; Hendrizan, Marfasran; Rachmayani, Rima; Napitupulu, Gandhi (BULLETIN OF THE MARINE GEOLOGY, 2024)
Indonesian Throughflow (ITF), which is part of the global thermohaline circulation, is known to play an important role in the heat exchange between the Pacific and Indian Oceans. The flow of the ITF is highly complex, it depends on temperature and salinity. This study presents a proxy study from 25,000–18,000 years ago from two sites that are connected by the Indonesian Throughflow in the Makassar Strait. Oceanographic characteristics, including Sea Surface Temperature (SST) and Sea Surface Salinity (SSS) were reconstructed and analyzed during the Last Glacial Maximum (LGM) period. A 295 cm marine sediment core coded SO217-18522 (1°24.106'N; 119°04.781'E, water depth 978 m) and SO217-18519 (0°34.329'N; 118°06.859'E, water depth 1658 m) from the SONNE 217 research cruise in 2011 was used as research material. Oxygen isotope  analysis, planktonic foraminiferal Mg/Ca geochemistry, and radiocarbon dating were used in this study. The SST reconstruction shows that the temperature during the LGM reach the minimum during ~20 ka BP and the SST value was significantly lower by ~2–3 °C compared to the Late Holocene value. The SST also shows significant cooler in marine sediment SO2017-8519 located in the southern site compared to the northern site. Salinity reconstructions during the LGM shows that SSS value was 0.82–1.13 psu higher than in the Holocene. The south–north gradients of SST and SSS in the Makassar Strait were larger over the 23.2–24.2 ka BP (SST gradient by 0.5–1 °C and SSS gradien by 1–1.7 psu) compared to the Late Holocene. The increase in SST and SSS gradients during the ~20 ka BP likely indicates a weakened intensity of the surface ITF relative to conditions during the Late Holocene.